Interpersonal conflict, values, strategies for overcoming stress situations of students before and after the start of a special military operation - E. F. Yashchenko (Вестник университета)
The article provides an overview the study of the problem of intrapersonal conflict, values  and strategies for overcoming stressful situations in the modern literature. The results of the author’s research identifying the psychological characteristics of students of a transport university before and after the start of a special military operation are presented. Using methods to identify the level of internal conflict A.I. Shipilov, “Strategies for overcoming stress situations SACS” S. Hobfall in the adaptation of N.E. Vodopyanova, E.S. Starchenkova; «The level of the ratio of “value” and “accessibility” in various life spheres» by E.B. Fantalova, «Freiburg multifactorial personal questionnaire FPI» by I. Farenberg, H. Zarg and R. Gampel in the adaptation of A.A. Krylov and T.I. Ronginskaya described and analyzed psychological portraits of students before the start of a special military operation and after its beginning. Before the start of a special military operation, students’ psychological characteristics are: confrontation of claims with their real potential, anxiety, entering into social contact to solve problematic situations, the value of real friends, focus on current events and male-type behavior, the desire to achieve the goals set, self-confidence, seeking social support, love, courage, and the pursuit of public recognition. The psychological portrait of students after the start of a special military operation includes a reduced critical attitude towards themselves, reduced anxiety, a decrease in the value of friends, greater aggressiveness in defending their interests, a decrease in social contacts, moral and adaptation conflict, conflict of motivation, obligation, lack of assertive actions, internal tension.